Efektivitas Pemilihan Raja Di Negeri Haruru Kecamatan Amahai Kabupaten Maluku Tengah - Rezita. A. N. Sapulette; Z. A. Rengifurwarin; Ivony Rahanra (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This research is descriptive qualitative type. Aims to analyze and explain the description of the Effectiveness of the Election of the King and the factors that influence it in Negeri Haruru, Amahai District, Central Maluku Regency. Informants of this study amounted to 8 people. The data needed in this study were collected through observation, interviews and documentation techniques. Data was successfully collected, processed and analyzed with the help of descriptive qualitative analysis techniques. The results of this study indicate that the level of effectiveness in the election of the King in Haruru Country is not good enough and not optimal as a whole. This is influenced by unfavorable factors such as: a) Differences in perceptions in society, b) guidance, mediation and facilitation by local governments, c) community compliance with customary values and rules. The implication of this research, if you want to optimally increase the level of effectiveness of the election of the king in Haruru country as expected, it is necessary to optimize the implementation of the factors that influence the process of selecting the king in question, properly and adequately as expected.